Values and religious experience: for an intercultural dialogue according to Viktor E. Frankl's perspective - Carlo Macale (University of Bologna, 2022)
The contemporary society is characterised by a strong presence of different religious expressions, both traditional and new, community-based and individual. Therefore, we speak of a post-secular age in which there is a continuous exchange between beliefs and non-beliefs in everyday life. In this sense, the religious question takes on an increasingly intercultural connotation in the continuous biographical exchanges among people who give different existential meanings according to their own conscience. It is precisely the dimension of meaning, determined by the choice of values, based on a perspective linked to Frankl's existential analysis and logotherapy, that will be the subject of this contribution. In particular, proposing a theoretical approach to the question (also based on empirical studies), we will outline what could be some aspects of Frankl's psychology useful to lay the foundation of an educational stance on religiosity that could promote a democratic and supportive coexistence within an intercultural horizon.